Preparation of conductive polymer graphite (PG) composites - Abdullah, Nur Munirah; Kamarudin, M Saddam; M Rus, Anika Zafiah; Abdullah, M F L (IOP Publishing, 2017)
The preparation of conductive polymer graphite (PG) composites thin film is described. The thickness of the PG composites due to slip casting method was set approximately ~0.1 mm. The optical microscope (OM) and fourier transform infra-red spectroscopy (FTIR) has been operated to distinguish the structure–property relationships scheme of PG composites. It shows that the graphite is homogenously dispersed in polymer matrix composites. The electrical characteristics of the PG composite were measured at room temperature and the electrical conductivity (σ) was discovered with respect of its resistivity (Ω). By achieving conductivity of 103 S/m, it is proven that at certain graphite weight loading (PG20, PG25 and PG30) attributes to electron pathway in PG composites.